Rambutan related ocular trauma - Abdurrahman, Muhammad Yusuf; Rosli, Abdul Hadi; Mohd. Kamal, Khairidzan (2021)
Rambutan trees are widely planted in rural areas. Regardless of the small size, its physical characteristics may inflict ocular trauma when it accidentally hit the eyes. We report a case of a 61-year-old gentleman who suffered from a right eye deeply embedded cornea foreign body and fungal keratitis following direct ocular trauma by rambutan fruit. He complained of right eye pain with reduced vision after being alleged hit by rambutan fruit during harvesting from the tree. Upon slit-lamp examination, there were multiple woody-like cornea foreign bodies in which one of it had deeply embedded up to the deep stromal layer. Following uncomplicated cornea foreign bodies removal under general anaesthesia, the patient had developed fungal keratitis which was successfully treated with topical and oral antifungal. This report highlights the importance of prompt diagnosis and proper management of rambutan related ocular trauma. Early removal of cornea foreign body as well as early initiation of topical and systemic antibiotic and antifungal following vegetative material injury able to prevent more serious corneal infection and endophthalmitis.